STUDENTS’ ENTREPRENEURSHIP AS AN EXTERNAL EFFECT OF HIGHER EDUCATION INSTITUTION ON THE CASE OF STATE SCHOOL IN BIAŁA PODLASKA - Adamowicz, Mieczysław (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Entrepreneurship at the university, may be recognised both in the group of teachers/researchers and among students. Students’ entrepreneurship is an important form of external effects of educational activity of the university. The aim of the paper is to define the predisposition of students of State School of Higher Education in Biała Podlaska for entrepreneurship activity during studying. Second aim is an assessment of the ability of the school to create the framework and conditions for academic entrepreneurship. Sources of information for research were subject literature, official documents and information from the school and own survey among students.Research results show that academic entrepreneurship is rather poor and reasons for that are on both sides – dissatisfied students’ attitudes to business activity and weak school support for these external effects of educational activity. Investigation proved that there are large areas for improvements.